Ayurvedic Management of Depressive Disorder – A Case Study - M. Chabanur, Sunilkumar; Dipankar, D.G. (Journal of Neonatal Surgery, 2025)
Depressive Disorder (DD) is a persistent and episodic condition characterized by disturbances in mood, interest, cognition, and vegetative functions. It significantly impacts patients' quality of life, influencing their physical, mental, personal, social, and spiritual well-being. The terms Vishada and Avasada refer to milder depressive episodes and can be likened to Kaphaja Unmada. The current case presented involved symptoms of sadness, feelings of worthlessness, helplessness, thoughts of death, and disrupted sleep, leading to a diagnosis of DD according to DSM V criteria. The Ayurvedic assessment identified Kaphaja Unmada, indicating an imbalance of kapha-dominant vata and tama dosha. A mental examination revealed disturbances in mana (mind), buddhi (intellect), smriti (memory), bhakti (desire), sheela (temperament), chest (psychomotor activity), and achara (conduct). The patient was classified as Avara Satwa. The management plan included Ayurvedic treatments, specifically Yuktivypasharaya (pharmacological approach), utilizing Ghritapaana and Pratimarsha Nasya with Panchapavya Ghrita. The treatment spanned 30 days, incorporating both Ghritapaana and Pratimarsha Nasya. Follow-up assessments indicated a significant reduction in Hamilton depression rating scores from 31 to 6. The patient's self-reported anxiety decreased by the 10th day, and by the 30th day of treatment, there was a notable remission. Improvements were maintained even during the non-interventional observation period. Therefore, the Ayurvedic integrative management demonstrated effectiveness in treating DD.